Respuesta :
Answer:
3.(-6,-8)
Step-by-step explanation:
y=x-2
2x+4=y
x-2=2x+4
x=2x+6
-x=6
x=-6
y=-6-2
y=-8
Step 1: Wherever you see a y in the equation: 2x + 4 = y insert x - 2
2x + 4 = x - 2
Step 2: Combine like terms
x's go with x's. To do this subtract the x from the right side to both sides
(2x - x) + 4 = (x - x) - 2
x + 4 = 0x - 2
x + 4 = -2
Normal numbers go with normal numbers (4 and -2). Bring the 4 to the right side by subtracting it to both sides
x + (4 - 4) = -2 - 4
x + 0 = -6
x = -6
Step 3: To solve y put -6 where you see an x in the equation: y = 2x + 4
y = 2(-6) + 4
y = -12 + 4
y = -8
(-6,-8)
Hope this helped!